2018
DOI: 10.1111/jace.15754
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature crystallization of La0.15Sr0.775TiO3 using ionic liquids

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution (CC BY) licence. This licence allows you to distribute, remix, tweak, and build upon the work, even commercially, as long as you credit the authors for the original work. More information and the full terms of the licence here: https://creativecommons.org/licenses/ Takedown If you consider content in White Rose Research Online to be in breach of UK law, please notify us by emailing eprints@whiterose.ac.uk including the URL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They successfully synthesised a range of nanoscale complex oxides using this technique, including sodium potassium niobate, and importantly, demonstrated that aqueous solutions of precursor metal salts could be combined with alkoxide precursors (with an intermediate heating step to drive off water for the aqueous salts), without the detrimental and often violent formation of binary oxide materials. More recently, Mottram et al 31 showed that the addition of cellulose to this reaction was not needed, by showing that nanoscale templating in La-doped strontium titanate could be achieved using the ionic liquid alone, further simplifying the reaction mixture. Thus this non-aqueous synthesis route shows substantial promise for use in the synthesis of nanoscale titanate materials.…”
Section: Introductionmentioning
confidence: 99%
“…They successfully synthesised a range of nanoscale complex oxides using this technique, including sodium potassium niobate, and importantly, demonstrated that aqueous solutions of precursor metal salts could be combined with alkoxide precursors (with an intermediate heating step to drive off water for the aqueous salts), without the detrimental and often violent formation of binary oxide materials. More recently, Mottram et al 31 showed that the addition of cellulose to this reaction was not needed, by showing that nanoscale templating in La-doped strontium titanate could be achieved using the ionic liquid alone, further simplifying the reaction mixture. Thus this non-aqueous synthesis route shows substantial promise for use in the synthesis of nanoscale titanate materials.…”
Section: Introductionmentioning
confidence: 99%